Development of nonlinear analytical model and seismic analyses of a steel frame with self-centering devices and viscoelastic dampers - Karavasilis, T; Blakeborough, T; Williams, M (2011)
This paper highlights the role of advanced structural analysis tools on the conception of high-performance earthquake-resistant structural systems. A new steel frame equipped with self-centering devices and viscoelastic dampers is described. A prototype building using this frame is designed and a detailed nonlinear analytical model for seismic analysis is developed. Seismic analyses results show the effectiveness of the proposed frame to enhance structural and non-structural performance by significantly reducing residual drifts and inelastic deformations, and by reducing drifts, total floor accelerations and total floor velocities. These results are the basis for further studies aiming to develop design methods and criteria for the proposed high-performance frame. © 2010 Elsevier Ltd. All rights reserved.